PSMA-based theranostics in diagnosing and treating prostate cancer in the Asian male population: a narrative review - Liu, Feng; Ge, Chang; Qiao, Bingzhang; Aihemaiti, Zubeila; Li, Zhao; Zhang, Weijie; Zebibula, Abudureheman; Rexiati, Mulati (Frontiers in Oncology, 2025)
Prostate-specific membrane antigen (PSMA) is a protein primarily overexpressed on the surface of prostate cancer (PCa) cells, making it a key target for PSMA-based theranostics, which combine diagnostic imaging and therapy. PSMA-based molecular probes, conjugated tracers and isotopes, and multifunctional imaging technologies have significantly advanced the landscape of high-risk PCa management, particularly during initial diagnosis and treatment planning. This tool is especially crucial as the ratio of mortality to incidence of PCa in Asian populations is higher, and the overall prognosis is significantly worse compared to Western countries. Furthermore, prostate-specific antigen (PSA) screening using multiparametric magnetic resonance imaging (MRI) and pathological examination shows that only a small percentage of men (below 30%) with PSA levels between 4–10 ng/ml in China, considered low risk, actually test positive for PCa when biopsied. Therefore, PSMA ligand-based positron emission tomography (PET) has been increasingly utilized for the accurate diagnosis, clinical staging, dynamic monitoring, treatment guidance, and prognosis evaluation of PCa. Moreover, PSMA-targeted radioligand therapy (RLT), antibody-drug conjugate (ADC) therapy, cellular immunotherapy, photodynamic therapy (PDT), and photothermal therapy (PTT), along with PSMA radioguided surgery (PSMA-RGS) intervention, have shown substantial advantages and promising potential. The field of PSMA ligands in PCa management has seen remarkable advancements in recent years, impacting both diagnostic and therapeutic approaches. This review discusses and summarizes the recent research progress and application prospects of PSMA-based theranostics in the clinical management of PCa in Asian populations.